Tourism Wellness Industry as Local Culture in Millenial Perspective at Tourism Polytechnic in Bali - Ni Desak Made Santi Diwyarthi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This ongoing research reveals the perspective of millennial student at Tourism Polytechnic, especially Politeknik Pariwisata Bali toward wellness industry. The purpose of this research is looking for interesting things in terms of the health industry for millennials. The respondent was the leader of semester 8, four student from Hospitality Management Study Program. The research used depth-interviews, observation, and study documents. The conclusions were wellness industry is highly appealing to millennials due to its focus on health, meaningful experiences, environmental consciousness, stress management, and social connection. Millennials’ values align with the offerings of the wellness industry, making it a significant choice for this generation.